Within the frame : the journey of photographic vision - DuChemin, David (New Riders, 2009)
Both instructional and inspirational, Within the Frame helps you on your photographic journey to make better images of the places and people you love, whether they are around the world or in your own backyard. duChemin covers how to tell stories, and the technology and tools we have at our disposal in order to tell those narratives. --from publisher description.